2013
DOI: 10.1016/s0325-7541(13)70034-8
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide resistance in Streptococcus pneumoniae isolated from Argentinian pediatric patients suffering from acute otitis media

Abstract: Macrolide-resistant Streptococcus pneumoniae emerged in Argentina in 1995, representing 26% of invasive infection isolates in children under 5 years old. The objectives of this study were to describe the prevalence of ermB and mefA genes in macrolide-resistant S. pneumoniae isolates from acute otitis media (AOM) and to determine their genetic relatedness. Between May 2009 and August 2010, 126 S. pneumoniae isolates from 324 otherwise healthy children with a first episode of AOM were included. Twenty six of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…49 As oppose to a study conducted in India, 31 our study showed that isolates of S aureus were relatively more susceptible to erythromycin and co-trimoxazole. Streptococcus pneumoniae is an opportunistic pathogen that was resistant to erythromycin, thus coinciding with previous studies from Argentina 24 and Thailand. 51 Erythromycin is one of the antibiotics of choice for upper respiratory infections, pneumonia, and OM in PLH and children 42 ; such resistance may impede management of the infections leading to severe invasive diseases including bacteraemia and meningitis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…49 As oppose to a study conducted in India, 31 our study showed that isolates of S aureus were relatively more susceptible to erythromycin and co-trimoxazole. Streptococcus pneumoniae is an opportunistic pathogen that was resistant to erythromycin, thus coinciding with previous studies from Argentina 24 and Thailand. 51 Erythromycin is one of the antibiotics of choice for upper respiratory infections, pneumonia, and OM in PLH and children 42 ; such resistance may impede management of the infections leading to severe invasive diseases including bacteraemia and meningitis.…”
Section: Discussionsupporting
confidence: 78%
“…9,12,18 The most common OM pathogen, S pneumoniae , has been implicated as part of the current antibiotic resistance crisis. 23,24 Multidrug-resistant pathogens have also been isolated from patients with invasive infections, from immunosuppressed individuals, and from carriers. 25,26 Globalization (easy travel around the world) has further disseminated the antimicrobial-resistant microorganisms; hence, antimicrobial-resistant infections have become a global calamity.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of antibiotic resistance comprises disruption of the antibiotic passage into cells, which alters the target site of the antibiotic. The erm B gene is usually detected in enterococci strains recovered from clinical, environmental, and food sources and other Gram-positive cocci such as Staphylococcus aureus (Ding et al, 2012), Streptococcus pyogenes (Palmieri et al, 2012), or Streptococcus pneumoniae (Reijtman et al, 2013). Aside from the erm B gene, E. faecalis and E. faecium from food samples had a significant range of elements, which code for N -6 methyltransferase ( erm C; erm A) or those accountable for the enterococci efflux characteristics ( mef A/E; msr C).…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] In Argentina, the frequency of macrolide-resistant S. pneumoniae isolates increased from 9% in the 1997 to 1998 period to 16% between 2000 and 2002 and currently seems to be approaching 20%. 31,32…”
Section: Antibiotic Resistancementioning
confidence: 99%